Compliment-concept and discourse features of qualitative lexemes of human nature (on the example of German and Uzbek languages) - Habibullo Abdullaevich Baymanov; Malika Kuvandikovna Altibayeva (Periodica Journal, 2023)
This article explains the direct dependence of the level of national identity on the use of qualitative lexemes of human nature in the compliment-concept of German and Uzbek languages, sociopolitical discourses, the national mentality in it in the construction of languages. processed
Keywords: compliment-concept, socio-political discourse; adjective lexeme; cognitive; linguocultural